Proposal of an Urban Geotourism Itinerary in the UNESCO Global Geopark Volcanes de Calatrava, Ciudad Real (Castilla-La Mancha, Spain): “Volcanoes and Petra Bona (Piedrabuena)” - Darío Guevara; Rafael Becerra-Ramírez; Javier Dóniz-Páez; Estela Escobar (Land)
The need to promote proximity tourism in natural areas has made the destinations in the interior of the Iberian Peninsula a benchmark in the development of tourism in traditionally rural and depressed areas. In Ciudad Real province, a sustainable territorial management project was developed based on the uniqueness of its volcanic geoheritage, leading to its designation as the UNESCO Global Geopark “Volcanes de Calatrava, Ciudad Real”. Geoparks promote sustainable activities such as geotourism; thus, an urban geotourism itinerary was proposed in Piedrabuena (Ciudad Real, Castilla-La Mancha) in order to make the natural and cultural geoheritage of a part of the geopark known, which is also a part of the Campo de Calatrava Volcanic Region. For this purpose, 12 natural and cultural resources of the geoheritage of the Piedrabuena volcano, on which the urban centre is located, were identified, inventoried, characterized, and valorised as sites of geotouristic interest, and they were connected along a geotourism itinerary. This itinerary has a 4 km route and up to eight interpretive stops, which allows visitors and tourists to enjoy a geotourism experience based on the volcanic landscape of the geopark, laying the foundations for the creation of other similar experiences.